Ethical and Logistical Issues Raised by the Advanced Donation Program "Pay It Forward" Scheme. - ROSS, LAINIE FRIEDMAN; RODRIGUE, JAMES R.; VEATCH, ROBERT M. (Journal of Medicine & Philosophy, 2017)
The advanced donation program was proposed in 2014 to allow an individual to donate a kidney in order to provide a voucher for a kidney in the future for a particular loved one. In this article, we explore the logistical and ethical issues that such a program raises. We argue that such a program is ethical in principle but there are many logistical issues that need to be addressed to ensure that the actual program is fair to both those who do and do not participate in this program.